The Tudors : A Very Short Introduction - Guy, John (Oxford, New York Oxford University Press, 2013)
In this revised and updated edition of The Tudors: A Very Short Introduction, John Guy offers a compelling and authoritative guide to all aspects of the Tudor period. From politics, religion, and economics, to gender, art, and culture, this is a fascinating exploration of the leaders of the day and the culture of the time.
Include Illustration, Bibliography and Index
Keywords: Tudor, -- Familie -- History -- Great Britain -- History -- Tudors, 1485-1603.